Daughters of the American Revolution. Daniel Newcomb Chapter (Yankton, S.D.) dramatic scripts - Daughters of the American Revolution. Daniel Newcomb Chapter (Yankton, S.D.)
Scripts of historical broadcasts sponsored by the Daniel Newcomb Chapter (Yankton, S.D.) of the Daughters of the American Revolution.
Collection material in English.
Keywords: Drama -- Stories, plots, etc; Radio programs; Radio scripts